Opioid receptors in the rat spinal cord after longlasting deafferentation - Hájek, I; Buritová, J; Kríz, N (Physiological research, 1992)
In vitro binding of specific opioid ligands to their respective sites in membrane fractions and the contribution of individual receptor classes (mu, delta, kappa) was studied in rats after longlasting (up to 22 months) section of spinal dorsal roots at the cervical (C5-8) or thoracic (Th1-4) level. This procedure leads to autotomy or scratching of the skin on the operated side. The total number of receptors in the cervical and thoracic spinal cord was more than doubled in both operated and contralateral part of the cord in comparison with intact controls of the same age. In the cervical region, this increase mainly represented a rise in the number of free receptors, whilst in the thoracic region both free and saturated receptors were increased. On the deafferented side, receptor selectivity, especially in the delta and kappa types was decreased.
Keywords: potkani Wistar; následné studie; Follow-Up Studies; zvířata; Female; Spinal Cord; Denervation; diprenorfin; Ganglia, Spinal; mícha; Animals; krysa rodu Rattus; Rats; receptory opiátové; Rats, Wistar; ženské pohlaví; spinální ganglia; Receptors, Opioid; Diprenorphine; denervace